Comparison of clinicopathological features and outcomes in patients with primary leiomyosarcoma of bone and soft tissue. Issue 5 (1st February 2021) - Gusho, Charles A.; Blank, Alan T.; Gitelis, Steven
Abstract: Backgrounds and Objectives: This investigation sought to describe the outcomes of primary leiomyosarcoma of bone (PLB) compared to soft tissue leiomyosarcoma (SLMS). Methods: This was a review of the Surveillance, Epidemiology, and End Results database from 1975 to 2016. Kaplan‐Meier methods were used to estimate disease‐specific survival (DSS), and a Cox regression model was used to identify prognostic factors. Results: Of the 7502 identifiable cases, 1% ( n = 74) were PLB and 99% ( n = 7428) were SLMS. Survival was the same between PLB and SLMS ( p = .209). On multivariable analysis for high‐grade SLMS, radiation (neoadjuvant: hazard ratio [HR], 0.56; 95% confidence interval [CI], 0.4–0.8; p = .003; adjuvant: HR, 0.75; 95% CI, 0.6–0.9; p = .008) and surgery (procedure specific) improved DSS. For PLB, wide resection/limb salvage (HR, 0.40; 95% CI, 0.3–0.5; p = .018) and amputation (HR, 0.69; 95% CI, 0.5–0.9; p < .001) were positive prognostic factors. Neither radiation nor chemotherapy were prognostic factors for survival in PLB. Conclusions: For SLMS, radiation portends a survival advantage. For PLB, however, neither chemotherapy nor radiation were significant prognostic factors, which suggests the optimal treatment for PLB, similar to other primary soft tissue sarcomas originating in bone, remains an unmet medical need.